The Risk Factors Affecting Disability Level of Lumbar Disc Herniation - Melda Yelmaiza; Restu Susanti; Syarif Indra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Lumbar disc herniation (LDH) is a disorder that involves rupture of the annulus fibrosus so that the nucleus pulposus protrudes and compresses the lumbar canal. LDH is the most common cause of lumbar radiculopathy. LDH causes functional disorders in patients, causing disability to carry out daily activities. The purpose of this study was to determine the risk factors that influence the degree of disability in lumbar nucleus pulposus herniation. Methods. Analytical research with a consecutive cross-sectional study approach in patients with lumbar LDH at the Neurology Outpatient Clinic, Dr. M. Djamil General Hospital Padang from March to November 2021. The risk factors assessed were age, gender, occupation, length of illness, and body mass index (BMI). The measurement of the degree of disability uses the Oswestry disability index (ODI) score. The relationship between risk factors and the degree of disability was analyzed using chi-square test. Differences in the mean age of groups with mild and moderate degrees of disability using unpaired t-test. Results. 40 subjects met the inclusion and exclusion criteria. Mean age 57 ± 10,976 years, male and female ratio 1:2, work with heavy lifting activities was found in 70% of subjects, duration of suffering from LDH more than one year in 60% of subjects. BMI overweight and obesity as many as 77.5% subjects. As many as 60% of the subjects experienced mild to moderate degrees of disability. There is a difference in the average age of the subjects with mild to moderate degree of disability with a severe degree of p-value of 0.044. There was no significant relationship between gender (p=0.054), occupation (p=0.398), length of illness (p=0.503) and body mass index (p=0.757), and the degree of disability. Conclusion. The degree of disability in patients with LDH is influenced by age. Meanwhile, gender, occupation, length of illness and body mass index were not significantly related to the degree of disability in patients.